The effectiveness analysis of traditional and new landscape indexes in indicating flood risk of watersheds from the perspective of source-sink landscapes: A case study of Changsha, China - Lingxuan Zhang; Sheng Jiao; Jie Lu (Ecological Indicators)
Landscape patterns are a key factor influencing flood risk, yet existing studies primarily focus on the impact of blue-green landscape patterns, without systematically considering the effects of other landscape patterns. Furthermore, most research relies on traditional indexes in Fragstats to represent landscape patterns, emphasizing the correlation strength between indexes and flood risk, but lacking systematic evaluation of index effectiveness and ecological significance. To address these gaps, this study integrated source-sink theory with stormwater runoff processes and flood risk formation mechanisms. It selected effective traditional indexes from a source-sink perspective to indicate flood risk, revised the location-weighted landscape index (LWLI), and compared the effectiveness of new and traditional indexes in representing flood risk. The study proposed a new perspective and method to systematically explore the relationship between landscape patterns and flood risk. Results showed that over a 40-year period, landscape fragmentation and complexity increased. The source landscapes expanded by 680.84 km2, with significant growth and aggregation, primarily in low-lying areas near watershed outlets, while the sink landscapes evolved in the opposite direction. Among traditional indexes, the total patch area, mean patch size, and cohesion index were effective in indicating flood risk. The modified index demonstrated average correlation coefficients of 0.87 and 0.53 with surface runoff and high-risk flood areas, compared to 0.69 and 0.25 for traditional indexes, highlighting its superior effectiveness in indicating flood risk. This study identified effective traditional indexes and developed a new index based on flood risk formation mechanisms, advancing landscape pattern research in flood risk management from a source-sink perspective. The findings offer an effective ecological approach for stormwater management and provide valuable insights for optimizing landscape spatial patterns. These results have significant implications for enhancing urban disaster resilience and informing planning efforts. Furthermore, they can serve as a reference for flood risk management in other regions with similar conditions.